PROMOSI PEGAWAI NEGERI SIPIL DALAM JABATAN STRUKTURAL DI BIRO HUMAS DAN PROTOKOL KANTOR GUBERNUR KALIMANTAN BARAT - Tri Yunanda Setiadi E.01107104 (FISIP Universitas Tanjungpura, 2013)
This article is backgrounded about set of problems the requirements and the mechanism of promoting government staff for structural position in the bureau of protocol and public relation in West Kalimantan provincial office. The problem of this study is about the procedural process of assigning staff for structural job in the bureau of protocol and public relation in West Kalimantan provincial office. This is a descriptive study aiming to investigate and explain the procedure comprises recruitment, pre-selection, competency test, final selection and decision making. Observation, interview and documentation were used to collect the data which were then analysed qualitatively.The preliminary result of this reserrch shows that the implementation process of promoting structural position has undergone all of the procedures. However, the implementation of the process is far from ideal. It occurs due to political interest. Top level managers appoint staff for the structural position are based on the similar political interest and individual relationship not on their competence.Key words: Promotion, Government staff.